Guinea-Bissau Public Expenditure Review : Seizing the Moment - Managing Public Finance for Development - World Bank Group (World Bank, Washington, DC, 2019)
Guinea-Bissau is a small state in West Africa with a population of around 1.8 million. It is rich in natural resources (fisheries, forestry and agriculture) and biodiversity. Guinea-Bissau is host to a large variety of ethnic groups, languages and religions, with communal and ethnic-based violence remaining low. The country has a history of political and institutional fragility dating back to its independence from Portugal in 1973. Guinea-Bissau continues to face formidable development challenges, but resources remain very limited. Government spending on the social sectors is low, which, combined with low efficiency, translated into weak outcomes. The objective of the Guinea-Bissau Public Expenditure Review (PER) is to analyze government expenditure, fiscal revenue, and public financial management in selected sectors (education, health, and security). The sectors for analysis were selected based on a combination of factors, including spending trends, budget size, the country's development program, and World Bank engagement. The PER has been initiated by the World Bank and the team worked closely with the Ministry of Economy and Finance (MEF), and line ministries throughout the process. The PER is well aligned with the FY2018-2021 Country Partnership Framework (CPF). The first two objectives of the CPF are increased access to and quality of primary education, and increased access to and quality of maternal and health services. The CPF identifies limited fiscal space and weak PFM systems as being among the key challenges to improving access to quality social services. The PER also supports the fourth pillar of the Government's National Development Plan, Terra Ranka (Fresh Start), which aims to develop the human capital potential of the population. The three sectors under consideration together account for over thirty percent of government expenditure; thus, any efficiency improvements and/or expenditure savings in those sectors are likely to be substantial.